Unusual Metastatic Sites of Testis and Rectum in Prostate Cancer Detected by 68Ga-PSMA-11 PET/CT Imaging at Initial Staging - Parghane, Rahul V.; Basu, Sandip (World Journal of Nuclear Medicine, 2024)
Imaging plays a pivotal role in defining the extent of disease and deciding therapeutic strategies in recently diagnosed high-risk prostate cancer. Standard-of-care conventional imaging may often miss rare metastatic disease sites. We herein present a unique case of prostate cancer where 68Ga-PSMA-11 positron emission tomography (PET)/computed tomography (CT) detected two unusual metastatic sites (testis and rectum) in a single patient at initial staging, resulting in an accurate determination of the extent of disease, more tailored multimodal treatment planning, and exploration of the theragnostic potential.
Keywords: prostate cancer; prostate-specific membrane antigen; 68Ga-PSMA-11 PET/CT; theranostics; metastatic disease to the testes and rectum